The Effect Of Trading Volume Activity, Stock Price, Dividend, Earning Per Share, And Variance Of Return To Bid-Ask Spread (Studies in LQ-45 Company in the Indonesia Stock Exchange) - Eliza Chozna Ulfaniza; Erna Listyaningsih (Universitas Malahayati, 2017)
This study aims to identify and provide empirical evidence about the influence of the tradingvolume activity, stock price, dividend, earning per share, and variance of return to the bid-ask spread.Objek this research are the companies listed in the LQ-45 in the Stock Exchange Indonesia.This study is classified as quantitative research. The population in this study are all companies listedin the LQ-45 2011-2015. The sample is determined by purposive sampling method, as many as 22companies. Data obtained directly by downloading the company's financial statements LQ-45 whichhas been published in the Indonesia Stock Exchange. Data were analyzed using multiple linearregression analysis.These results indicate that the test is individually variable trading volume activity, dividend andvariance of return influence the direction of a positive coefficient significant to the bid-ask spread,while testing the individually variable stock price, and earnings per share does not affect the bid-askspread , Testing together five variables of trading volume activity, dividend, variance of return, stockprice, and earnings per share significantly affect the bid-ask spread